Prevalence of Treponema pallidum among Patient samples tested in the Haematology Laboratory, Usmanu Danfodiyo University Teaching Hospital, Sokoto - Musa, S.*, Adias, T.C., Ndakotsu, M.A., Ibrahim, K.K., Ikhuenbor D., Buhari A.H., Zama, I.I (Sokoto Journal of Medical Laboratory Science)
Syphilis is a sexually transmitted disease (STD) caused by the bacterium Treponema pallidum. Syphilis can cause long-term complications if not adequately treated. There was paucity of data on prevalence of syphilis infection in Sokoto, north western Nigeria. The aim  of this study is to determine the prevalence of syphilis among 400 blood specimens received at the Haematology Laboratory in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto. Gender distribution of subjects indicated that 240 were male while 160 were females. Syphilis was determined using CTK Biotech, Rapid test kit. Data was analyzed using SPSS ver. 20.There was zero prevalence of syphilis among blood specimens received. In conclusion, this study indicates a significantly low prevalence of syphilis among samples tested in the Haematology Laboratory in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto. There is need however for laboratory staff to continue to wear relevant personal protective equipments as well as observe universal precaution when dealing with patient samples.